Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1046/j.1464-410x.1998.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of mid‐ and lower ureteric calculi: extracorporeal shock‐wave lithotripsy vs laser ureteroscopy. A comparison of costs, morbidity and effectiveness

Abstract: Objectives To determine the eBcacy and costs of extraureter in 24 patients and in the lower ureter in 80. The outcome was assessed by stone-free rates, corporeal shock-wave lithotripsy (ESWL) compared with ureteroscopy (URS) in the treatment of mid-and re-treatment rates, time to become stone-free, complications and costs. lower ureteric calculi. Patients and methods The records of patients treatedResults ESWL for mid-and lower ureteric calculi resulted in a success rate of 90% and 81%, respectively, primarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
2
8

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(80 citation statements)
references
References 12 publications
4
66
2
8
Order By: Relevance
“…2 Although URS is a more invasive treatment option than ESWL, the success rate of the latter is probably lower, especially for mid and distal ureteral stones. 3,4 To date, ESWL, as a first-line therapeutic option, applied rapidly after the onset of renal colic, has been given very limited attention. Only two randomized trials have been reported, both with encouraging results, even if most cases were of proximal ureteral stones.…”
mentioning
confidence: 99%
“…2 Although URS is a more invasive treatment option than ESWL, the success rate of the latter is probably lower, especially for mid and distal ureteral stones. 3,4 To date, ESWL, as a first-line therapeutic option, applied rapidly after the onset of renal colic, has been given very limited attention. Only two randomized trials have been reported, both with encouraging results, even if most cases were of proximal ureteral stones.…”
mentioning
confidence: 99%
“…Planning the research design, werelied on experimental and clinical facts, obtained earlier, notably: during the experiment the new electro pulse RCL method demonstrated high effectiveness in analogous sandcement mixture stone models destruction, including the samples consisting of 100% cement, during the singular pulse exposure with the power of 0.1 to 0.45 J [8,9]. Such pulse power is comparable with the power of pulses, generated by the most safe RCL types, the pneumatic and laser ones (0.1 -0.14 J and 0.12 -0.5 J, respectively) [1,4,6,7,10].…”
Section: Discussionmentioning
confidence: 99%
“…In 2006 the electro pulse method which was offered as a new way of contact lithotripsy, which looked like splitting up the nephrolith by the exposure of the solid body by the electro pulses of nanosecond duration [5]. The radical difference of the new lithotripsy method from the highly effective, but unsafe because of high pulse power, electrohydraulic RCL and remote lithotripsy (RL) [6,7], is exposure on the nephrolith surface, not on the fluid environment with the shockwave creation, affecting the stone. According to the experimental research data, carried out on the analogous nephrolith models, the change of solid body exposure pattern from mediated to direct allows to decrease power and number of electrical pulses, required for the effective lithotripsy, significantly [8].…”
Section: Introductionmentioning
confidence: 99%
“…2 The choice of URS as a first-line therapy for distal ureteral calculi relies on the higher success rate, less fluoroscopy time and time to achieve a stone-free state. 2,4,13,14 Ureteroscopy is also less costly than ESWL for stones at all ureteral locations. 15 The high cost of purchasing and maintaining a lithotriptor is responsible for the high treatment cost associated with ESWL.…”
Section: Discussionmentioning
confidence: 99%